If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2y + -5)(6 + -3y) = 0 Reorder the terms: (-5 + 2y)(6 + -3y) = 0 Multiply (-5 + 2y) * (6 + -3y) (-5(6 + -3y) + 2y * (6 + -3y)) = 0 ((6 * -5 + -3y * -5) + 2y * (6 + -3y)) = 0 ((-30 + 15y) + 2y * (6 + -3y)) = 0 (-30 + 15y + (6 * 2y + -3y * 2y)) = 0 (-30 + 15y + (12y + -6y2)) = 0 Combine like terms: 15y + 12y = 27y (-30 + 27y + -6y2) = 0 Solving -30 + 27y + -6y2 = 0 Solving for variable 'y'. Factor out the Greatest Common Factor (GCF), '3'. 3(-10 + 9y + -2y2) = 0 Factor a trinomial. 3((-5 + 2y)(2 + -1y)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-5 + 2y)' equal to zero and attempt to solve: Simplifying -5 + 2y = 0 Solving -5 + 2y = 0 Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 2y = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 2y = 0 + 5 2y = 0 + 5 Combine like terms: 0 + 5 = 5 2y = 5 Divide each side by '2'. y = 2.5 Simplifying y = 2.5Subproblem 2
Set the factor '(2 + -1y)' equal to zero and attempt to solve: Simplifying 2 + -1y = 0 Solving 2 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1y = 0 + -2 -1y = 0 + -2 Combine like terms: 0 + -2 = -2 -1y = -2 Divide each side by '-1'. y = 2 Simplifying y = 2Solution
y = {2.5, 2}
| 8-c=2 | | (2x+3)(2x+3.25)-9.75=15 | | 9(x+7)-7=56 | | 3a-4=a-14 | | 6(g)=36 | | 2x+3=y+2 | | 3(x-3)=8 | | -m=6(m+7) | | 3+f=12 | | (7x)=(5x+18) | | 3/4(6)= | | 50=2x-2+x+2x-2+x | | 1.5y=60-4x | | 20=-3(m-4)+11 | | 4x-20=-42 | | 5-6=-11+2x | | -9x-1=18 | | 95y=64x | | 14=-2(m-1)+6 | | y=95x+64 | | 11t+3-8t=40-3t-1 | | 3x^2-18x=48x | | y=3/5 | | y=95+64x | | -4-20+19t=-20t-7(-7-18) | | 3b-12=-6 | | 16.2-3p=57.8 | | v+5.34=5.39 | | -5a-35=5 | | y=95+64 | | -5=5(p+8) | | 10d+2+1-9=94 |